EphB6 receptor modulates micro RNA profile of breast carcinoma cells. - Lokesh Bhushan; Raj P Kandpal (PLoS ONE, 2011)
Breast carcinoma cells have a specific pattern of expression for Eph receptors and ephrin ligands. EphB6 has previously been characterized as a signature molecule for invasive breast carcinoma cells. The transcription of EphB6 is silenced in breast carcinoma cells and its re-expression leads to decreased invasiveness of MDA-MB-231 cells. Such differences in phenotypes of native and EphB6 expressing MDA-MB-231 cells relate to an altered profile of micro RNAs. Comparative hybridization of total RNA to slides containing all known miRNAs by using locked nucleic acid (LNA) miRCURY platform yielded a significantly altered profile of miRNAs in MDA-MB-231 cells stably transfected with EphB6. After applying a threshold of change and a p-value of <0.001, the list of significantly altered miRNAs included miR-16, miR-23a, miR-24, miR-26a, miR-29a, miR-100, miRPlus-E1172 and miRPlus-E1258. The array-based changes were validated by real-time qPCR of miR-16, miR-23a, miR-24 and miR-100. Except miRPlus-E1172 and miRPlus-E1258, the remaining six miRNAs have been observed in a variety of cancers. The biological relevance of target mRNAs was predicted by using a common-target selection approach that allowed the identification of SMARCA5, SMARCC1, eIF2C2, eIF2C4, eIF4EBP2, FKABP5, FKBP1A, TRIB1, TRIB2, TRIB3, BMPR2, BMPR1A and BMPR1B as important targets of a subset of significantly altered miRNAs. Quantitative PCR revealed that the levels of SMARCC1, eIFC4, eIF4EB2, FKBP1a, FKBP5, TRIB1, TRIB3, BMPR1a and BMPR2 transcripts were significantly decreased in MDA-MB-231 cells transfected with EphB6. These observations confirm targeting of specific mRNAs by miR-100, miR-23a, miR-16 and miR-24, and suggest that the kinase-deficient EphB6 receptor is capable of initiating signal transduction from the cell surface to the nucleus resulting in the altered expression of a variety of genes involved in tumorigenesis and invasion. The alterations in miRNAs and their target mRNAs also suggest indirect involvement of EphB6 in PI3K/Akt/mTOR pathways.